Samuel Beckett and the visual arts - Carville, Conor, 1967- (Cambridge, United Kingdom : Cambridge University Press, 2018)
This book outlines Beckett's passion for the visual arts as he developed his signature style between the 1930s and 1970s.
Samuel Beckett and the Visual Arts is the first book to comprehensively assess Beckett's knowledge of art, art history and art criticism. In his lifetime Beckett thought deeply about visual culture from ancient Egyptian statuary to Dutch realism, from Quattrocento painting to the modernists and after. Drawing on a wide range of published and unpublished sources, this book traces in forensic detail the development of Beckett's understanding of painting in particular, as that understanding developed from the late 1920s to the 1970s. In doing so it demonstrates that Beckett's thinking about art and aesthetics radically changes in the course of his life, often directly responding to the intellectual and historical contexts in which he found himself. Moving fluently between art history, philosophy, literary analysis and historical context, Samuel Beckett and the Visual Arts rethinks the trajectory of Beckett's career, and reorients his relationship to modernism, late modernism and the avant-gardes.
PublicationsArchival Material; General Bibliography; Index.
Includes bibliographical references (pages 245-258) and index.
eBooks on EBSCOhost
Keywords: Beckett, Samuel, -- 1906-1989 -- Knowledge -- Art; Beckett, Samuel, -- 1906-1989; Art and literature -- Ireland -- History -- 20th century; Arts, Modern -- 20th century; Arts, Modern; Art et littérature -- Irlande -- Histoire -- 20e siècle.; Arts -- 20e siècle.; LITERARY CRITICISM -- European -- French; Art; Art and literature; Arts, Modern; Ireland; 1900-1999; History